Case report of drug induce erythroderma in diabetic patient: Erythroderma (World Journal of Current Medical and Pharmaceutical Research, 2023)
Erythroderma, a severe form of skin reddening, is often difficult to diagnose and is usually caused by underlying inflammatory skin conditions. In this case report, we present the management of a patient diagnosed with drug-induced erythroderma. The patient developed generalized redness and scaling 21 days after receiving an unknown injection for pain from a local pharmacy. A thorough history and clinical examination were conducted, and drug-induced erythroderma was suspected. The patient was treated with a combination of mid-potency corticosteroids, liquid paraffin, recombinant human epidermal growth factor, and oral antihistamines. The patient recovered after strict diabetic diet control and was discharged